Climate change impacts on the predicted geographic distribution of Betula tianschanica Rupr - Zhou, Hang; Li, Ao; Luo, Xuequn; Wang, Jiafeng; Xie, Yihong; Lin, Zhongping; Hua, Donglai (Frontiers in Plant Science, 2025)
IntroductionBetula tianschanica Rupr. is distributed in regions such as China, Kyrgyzstan, and Tajikistan. Owing to the impacts of climate change, it is increasingly threatened by habitat fragmentation, resulting in a precipitous decline in its population. Currently listed as endangered on the Red List of Trees of Central Asia, this species is predominantly found in the Tianshan Mountains. Examining the influence of climate change on the geographical distribution pattern of Betula tianschanica is crucial for the management and conservation of its wild resources.MethodsThis study employed two models, maximum entropy (MaxEnt) and random forest (RF), combined with 116 distribution points of Betula tianschanica and 27 environmental factor variables, to investigate the environmental determinants of the distribution of Betula tianschanica and project its potential geographical distribution areas.ResultsThe MaxEnt model and the RF model determined the primary environmental factors influencing the potential distribution of Betula tianschanica. The MaxEnt model showed that the percentage of gravel volume in the lower soil layer and elevation are the most significant, while the RF model considered elevation and precipitation of the wettest quarter to be the most crucial. Both models unanimously asserted that elevation is the pivotal environmental element affecting the distribution of Betula tianschanica.The mean area under the curve (AUC) scores for the MaxEnt model and RF were 0.970 and 0.873, respectively, revealing that the MaxEnt model outperformed the RF model in predictive accuracy. Consequently, the present study employed the estimated geographical area for Betula tianschanica modeled by the MaxEnt model as a reference. Following the MaxEnt model’s projected outcomes, Betula tianschanica is mainly located in territories such as the Tianshan Mountains, Ili River Basin, Lake Issyk-Kul, Turpan Basin, Irtysh River, Ulungur River, Bogda Mountains, Kazakh Hills, Lake Balkhash, Amu River, and the middle reaches of the Syr River.Within the MaxEnt model, the total suitable habitat area exhibits growth across all scenarios, with the exception of a decline observed during the 2041–2060 period under the SSP2-4.5 scenario. Remarkably, under the SSP58.5 scenario for the same timeframe, this area expands significantly by 42.7%. In contrast, the RF model demonstrated relatively minor fluctuations in the total suitable habitat area, with the highest recorded increase being 12.81%. This paper recommends establishing protected areas in the Tianshan Mountains, conducting long-term monitoring of its population dynamics, and enhancing international cooperation. In response to future climate change, climate refuges should be established and adaptive management implemented to ensure the survival and reproduction of Betula tianschanica.